Endogenous testosterone does not improve prediction of incident cardiovascular disease in a community-based cohort of adult men: results from the Tehran Lipid and Glucose Study. (1st October 2020) - Hatami, Hossein; Parizadeh, Donna; Bidhendi Yarandi, Razieh; Tohidi, Maryam; Ramezani Tehrani, Fahimeh
Abstract: Introduction: To explore the predictive value of testosterone added to the Framingham Risk Score (FRS) for cardiovascular disease (CVD). Methods: Among 816 men, 30–70 years/old, without prevalent CVD, from a community-based cohort (Tehran Lipid and Glucose Study), we assessed the predictive value of testosterone with incident CVD, using three multivariate Cox proportional-hazards models. Model I: FRS variables; model II: Model I plus total testosterone; model III: Model II plus Systolic blood pressure (SBP) * total testosterone (the best fit interaction-term between testosterone and FRS variables). Discriminations and goodness-of-fit were assessed by the C-statistic and the approach of Grønnesby, respectively. p Value <.05 was significant. Results: During 12 years of follow-up, 121 CVD events occurred. In all models, age, treated SBP, smoking, and diabetes were associated with increased CVD ( p values <.05). Neither testosterone (models II and III), nor SBP * testosterone (model III) were associated with CVD ( p values >.05). The C-statistics for models I, II, and III were 0.819, 0.820, and 0.821, respectively, indicating no significant improvement in the discrimination power. The models' goodness-of-fit did not improve compared with the FRS. Conclusion: Testosterone could not add to the predictive value of FRS for CVD in men, either directly, or through interactions with FRS variables.